Analysis of the effect of financial literacy and financial behavior on the performance of MSMEs Setu Babakan with digital competency as a moderating variable - Mulyadi, Mulyadi; Hendratni, Tyahya Whisnu; Wulandjani, Harimurti (Edelweiss Applied Science and Technology, 2024)
This study aims to analyze the effect of financial literacy and financial behavior on the performance of MSMEs in Setu Babakan, with digital competence as a moderating variable. MSMEs have an important role in the Indonesian economy, especially in creating jobs and supporting the local economy. In the Setu Babakan area, MSMEs face challenges such as limited digital literacy, business capital, and weak financial management. This research uses a survey method with a quantitative approach, collecting data from 60 MSME respondents, and testing hypotheses using the SEM-PLS (Partial Least Square) model. The results showed that financial literacy does not significantly influence the performance of MSMEs, while financial behavior has a positive effect on performance. Digital competency is proven to improve MSME performance, but cannot moderate the relationship between financial literacy and behavior with MSME performance. The implications of this study indicate the importance of financial behavior training and strengthening digital competencies for MSMEs. These results can be a reference for regional managers and universities to support digital competency training and financial management for MSME actors, so their performance can be more optimal in facing business competition.